PENGELOLAAN SANGGAR CUT NYAK DHIEN DALAM MENGEMBANGKAN KEBUDAYAAN ACEH (CUT NYAK DHIEN ATELIER MANAGEMENT IN DEVELOPING ACEH CULTURES) - Tengku Hartati (Mentari: Majalah Ilmiah Universitas Muhammadiyah Aceh, 2013)
Atelier is one of container in developing and preserving region cultures. This atelier aim is to preserving and developing region cultures by guiding and traditional art training to young generation. Its decrease and increase are depend on the human resource quality and others supporting means. Management knowledge is needed in atelier managing in order to get the maximal aim. This research aim is to know Cut Nyak Dhien atelier management in developing Aceh culture which relate to planning, implementation, organization, and supervision at Cut Nyak Dhien atelier Banda Aceh. This research uses qualitative approach with descriptive analysis method. The data collecting technique was done by interview, observation, and documentation study. The research subjects are atelier head, trainer, manager, and Cut Nyak Dhien atelierâ€™s elements. The research output shows: (1) Cut Nyak Dhien Atelier planning involve atelier head, trainer, and atelier managers. The program planning is according to its need and atelier aim. (2) In applying atelier program, the head, trainer, managers, and elements always have coordination. (3) Organizing is done with gather and arrange all resource which is needed include the human resource. (4) Supervision is done directly and indirectly by the head and Cut Nyak Dhien atelier coordinator.Â Keyword: atelier management and cultures development